TRAIL and curcumin codelivery nanoparticles enhance TRAIL-induced apoptosis through upregulation of death receptors - Xi Yang; Zhaojun Li; Qinjie Wu; Shouchun Chen; Cheng Yi; Changyang Gong (Taylor & Francis Group, 2017)
Active targeting nanoparticles were developed to simultaneously codeliver tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) and Curcumin (Cur). In the nanoparticles (TRAIL-Cur-NPs), TRAIL was used as both active targeting ligand and therapeutic agent, and Cur could upregulate death receptors (DR4 and DR5) to increase the apoptosis-inducing effects of TRAIL. Compared with corresponding free drugs, TRAIL-Cur-NPs group showed enhanced cellular uptake, cytotoxicity and apoptosis induction effect on HCT116 colon cancer cells. In addition, in vivo anticancer studies suggested that TRAIL-Cur-NPs had superior therapeutic effect on tumors without obvious toxicity, which was mainly due to the high tumor targeting and synergistic effect of TRAIL and Cur. The synergistic mechanism of improved antitumor efficacy was proved to be upregulation of DR4 and DR5 in tumor cells induced by Cur. Thus, the prepared codelivery nanoparticles may have potential applications in colorectal cancer therapy.